The Observation of Fast, Long Term, and Stable Performance of Toxic Absorption in Herbal Blessing Product Based on Galoba Maluku (Zingiberaceae Fruits) - Ido F Seay; Hendry Izaac Elim (SCIENCE NATURE, 2019)
The search for the best herbal medicine products for multitasking healing system associated with Galoba (Maluku language) or Golobe (North Maluku language) or zingiberaceae fruits are presented with a very systematic explanation after an intensive research in the last 3 years (~2016-2019) vary from its antioxidant content of flavonoid, chemical bonding organization, HIV virus medicine test, and toxic inhibition status. We obtained that the best herbal medicine produced in this paper called as Herbal Blessing products preparing with different system of Love herbal made by STIKES Halmahera, North Maliuku, Indonesia can provide fast, long term, and stable performance of toxic absorption. Such fast toxic response is an instantaneous process with no longer than 1 minute as well as a stable toxic binding for up to 4 months and 10 days so far. The obvious observation indicated few interesting physical chemistry processes during toxic absorption such as the nitrogen gas released during the sample preparation of Herbal Blessing, and the oxygen vanished in different sample processes of the same source of Murnaten Amomum sp. observed in a protected bottle consisted of the sample interaction with toxic in water. These amazing findings suggest that Herbal Blessing products are very promising for future multitasking healing system for human excellent health.